Universality of Dirichlet L-functions with shifted characters - Garunkštis, Ramūnas (Lietuvos matematikos rinkinys, 2004)
We study Dirichlet L-functions with shifted characters L(s, χ, H) = ⅀∞n=1 χ(n+H) ∕ ns, where H is an integer. Here we obtain a joint universality theorem for such functions.